2005
DOI: 10.1510/icvts.2004.100321
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for rupture of left ventricular free wall after acute myocardial infarction

Abstract: Left ventricular (LV) free wall rupture particularly in blow-out type is still one of the fatal complications after myocardial infarction. Seven patients had LV rupture following acute myocardial infarction. LV rupture was divided into two categories: blow-out type (true rupture) in 5 cases, or oozing type (incipient rupture) in 2 cases. All patients were in deep shock condition and underwent surgery on emergency basis. Patch and glue (fibrin glue) technique was applied for oozing type patients, while direct c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Recently, numerous reports about more conservative approaches such as epicardial patch with glue without CPB have been published with more successful outcomes 13,14 . However, surgical results depend on clinical presentation, prompt surgical repair, myocardial infarct size and state of ventricular tear 15‐19 . Four morphological types of rupture have been described 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous reports about more conservative approaches such as epicardial patch with glue without CPB have been published with more successful outcomes 13,14 . However, surgical results depend on clinical presentation, prompt surgical repair, myocardial infarct size and state of ventricular tear 15‐19 . Four morphological types of rupture have been described 20 .…”
Section: Discussionmentioning
confidence: 99%
“…28 The post-operative use of IABP, and other mechanical circulatory support, should always be taken into consideration because they can reduce the intra-cavitary pressure of the left ventricle, increase coronary blood flow and limit or prevent the development of low cardiac output syndrome. 17,31 Timóteo and colleagues reported that the use of IABP in patients with post-AMI mechanical complications was associated with improved in-hospital outcome. 32 However, the European Society of Cardiology/European Association for Cardio-Thoracic Surgery Guidelines on myocardial revascularization allocate short-term mechanical circulatory support, in the presence of post-AMI mechanical complications, in Class of recommendation IIb.…”
Section: Operative Strategiesmentioning
confidence: 99%
“…It may cause further injuries and also may decompensate the tamponade effect 12 16 17. The definitive treatment for this condition is surgical repair 1 12 18…”
Section: Discussionmentioning
confidence: 99%